School-Based Audio Clip Lessons in Social Studies for Modular Distance Learning - Amaro, Ailene Delos Santos (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Modular distance learning (MDL) poses significant challenges to teachers, parents, and students in the delivery of quality education in the country. The study evaluated the effectiveness of School-Based Audio Clip Lessons in Social Studies. It is an intervention program proposed to address the learning issues raised by parents of Grade 1 to Grade 6 MDL students at a public elementary school in Rizal, Philippines for the school year 2020-2021. Mixed methods research was used in the study. Results showed that the Audio Clip Lessons in Social Studies had a positive impact on the MDL learners (average MPS = 1.627), with an emphasis on the intervention being implemented across all learning areas in the school. Furthermore, the parents strongly agree that the use of Audio Clip Lessons is significantly beneficial and necessary for their children's studies. Thus, it is recommended that the use of audio clip lessons be implemented for the next school year across all grade levels in all learning areas. In addition, it is also suggested that funds be allocated to produce high-quality audio clip lesson materials and that marketing materials be used to encourage other schools to sign adopt the program.